2016
DOI: 10.1590/2177-6709.21.1.042-046.oar
|View full text |Cite
|
Sign up to set email alerts
|

Deflection test evaluation of different lots of the same nickel-titanium wire commercial brand

Abstract: Introduction: The aim of this in vitro study was to compare the elastic properties of the load-deflection ratio of orthodontic wires of different lot numbers and the same commercial brand. Methods: A total of 40 nickel-titanium (NiTi) wire segments (Morelli OrtodontiaTM - Sorocaba, SP, Brazil), 0.016-in in diameter were used. Groups were sorted according to lot numbers (lots 1, 2, 3 and 4). 28-mm length segments from the straight portion (ends) of archwires were used. Deflection tests were performed in an EMIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These findings were similar to the previous studies. [1617] Some studies have reported that the co-axial wires are viable alternative to the Titanium alloy,[181920] but in this study, the activation and deactivation forces of co-axial wires were incomparable at any point of deflection.…”
Section: Discussionmentioning
confidence: 67%
“…These findings were similar to the previous studies. [1617] Some studies have reported that the co-axial wires are viable alternative to the Titanium alloy,[181920] but in this study, the activation and deactivation forces of co-axial wires were incomparable at any point of deflection.…”
Section: Discussionmentioning
confidence: 67%